Teaching Grammar Effectively: Strategies for Success (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Living in a modern, globalized society, we know that learning foreign languages is very necessary for socializing with other foreign countries and having communication for different reasons, like business, study or travelling. While learning any other language, of course, grammar is considered as the most crucial part of learning process, because, grammar is the foundation of the language and meanwhile it can be a difficult obstacle for both teachers and students. Nevertheless, by using efficient teaching techniques, the difficult work of learning grammar may be made fun and approachable.